(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the level of nutritional knowledge and its association with the nutritional status and food consumption of hypertensive and/or diabetic patients at a Basic Health Unit in Maceió, Alagoas, Brazil. Methods: Cross-sectional study with a sample of individuals aged between 18 and 59 years. Demographic, socioeconomic, anthropometric (body mass index; waist circumference and; neck circumference), lifestyle, dietary and nutritional knowledge information were collected. Dietary data were collected using the food consumption frequency questionnaire. The nutritional knowledge score was stratified into “low knowledge”, “intermediate knowledge” and “sufficient knowledge”. A descriptive analysis of the variables was performed and the association between general nutritional knowledge, nutritional status, and food consumption was verified through analysis of variance, Tukey’s multiple comparison test, and Pearson’s correlation. Was considered significant p <0.05. The analyzes were performed in the R software. Results: Fifty-two patients were studied, of which 73.1% were female; 50% were economy class C2; 80.8% were sedentary. 53.8% had obesity, 82.7% had android adiposity, and 80.8% had high neck circumference. The consumption of servings of vegetables (1.78 servings) and dairy products (2.0 servings) was below the recommended (3 servings). 76.9% of the individuals had “intermediate” nutritional knowledge. Higher nutritional knowledge was associated with neck circumference within the normal range and greater consumption of fruits and vegetables. Conclusion: Higher nutritional knowledge was associated with a healthier diet profile and the anthropometric parameter neck circumference.